Education and Social Order: An Analysis of the Entrance Examination - Hsueh-Cheng Yen (National Taipei University of Education, 2014)
The article discusses two issues in Chinese education mobility: The emergence of the meritocracy ideal and its realization through the civil service examination. I propose that a theory of civilization contending a complex society must transcend the concentric model of kinship distance calculation in order to incorporate non-kin strangers into the enlarged social unit. The pre-Qin philosophers saw the problem when they argued against guanxi relationalism for it is ill-suited for organizing a complex society filled with strangers. In its stead, they proposed a ladder structure whereby strangers could be comparatively evaluated based on absolute standards and that one's position on the ladder should be the basis for the distribution of political power and material wealth. However, the upward mobility assumed in meritocracy was a threat to the privileged position of the dominant class. I argue the threat was transformed into an asset to the Chinese emperors through the civil service examination. By recruiting commoners to supplant the old guards in the court, the examination consolidated the power of the ruler at the expense of the reigning bureaucrats. Moreover, by encouraging commoners to compete in the examination, it also provided a low-cost means for the -integration of local societies. Contrary to the view that education mobility is a façade to disguise class reproduction, I argue it was an integral part of the Chinese political system which shaped the Chinese understanding of education.